KAPASITAS DAN PERILAKU PENGEMUDI DI LAJUR BERSAMA YANG MENGALAMI KONFLIK PADA SIMPANG DENGAN LAMPU LALU LINTAS - Prima Agusta, Budi
Abstract: A study of intersections with traffic signals in Indonesia carried out by the Indonesian Highway Capacity Manual project indicated that there is a large number of approaches intersections having shared lanes rather than exclusive right-turn lanes. The operation of shared lanes at an intersection within the same phase become complicated if the priority rule is not clear and the lane discipline is low. This study tries to observe the behaviour of right turning vehicles when they cross the intersection. Signal cycles in which the drivers did not cross the lane markings during their passage of the approach and the conflict area were used for \"lane by lane analysis\". The results were compared with the total data (\"approach analysis\"). An estimation of saturation flow based on lane by lane flow analysis is performed. The results indicate that during the green period all vehicles, from both directions, push to cross the intersection first. Around 60% - 70% of the first vehicle in a queue or around 30% - 40% of all the right turners force the opposing flow to give way when crossing the intersection. The results also indicate that the higher right turning vehicles in an approach, the lower the ERT values. The ERT values indicate the ability of the right turners, relative to straight through vehicles, to cross the intersection againts the influence of straight through opposing flows. From the results of ERT model, it seems that many right turning vehicles (60%-65% of total right turning vehicles) cross the intersection in a platoon. The saturation flow values were estimated using approach and lane by lane analysis. The results indicate that, generally Approach analysis give higher values of saturation flow than Lane by lane analysis. Generally the average difference of the saturation flow values calculated using approach and lane by lane analysis is around 20%. The higher PRTA values, the closer the difference of saturation flow values calculated using approach and lane by lane analysis. The PRTA value is a ratio between the number of right turners to the total vehicles in a studied approach at specified time period.